2017
DOI: 10.3389/fgene.2017.00057
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in the Ovarian Follicle

Abstract: The mammalian ovarian follicle is the complex reproductive unit comprising germ cell, somatic cells (Cumulus and Granulosa cells), and follicular fluid (FF): paracrine communication among the different cell types through FF ensures the development of a mature oocyte ready for fertilization. This paper is focused on non-coding RNAs in ovarian follicles and their predicted role in the pathways involved in oocyte growth and maturation. We determined the expression profiles of microRNAs in human oocytes and FF by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Therefore, toward a better understanding of apoptosis and autophagy may lead to more effective therapies for OA.Not only protein‐coding messenger RNAs (mRNAs), but also plenty of non‐protein‐coding transcripts, namely non‐coding RNAs consist of the human transcriptome . Long non‐coding RNAs (lncRNAs) are a class of transcripts with non‐protein‐coding capacity and 200 nucleotides in length . A variety of studies have demonstrated that lncRNA plays important roles in various biologic processes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, toward a better understanding of apoptosis and autophagy may lead to more effective therapies for OA.Not only protein‐coding messenger RNAs (mRNAs), but also plenty of non‐protein‐coding transcripts, namely non‐coding RNAs consist of the human transcriptome . Long non‐coding RNAs (lncRNAs) are a class of transcripts with non‐protein‐coding capacity and 200 nucleotides in length . A variety of studies have demonstrated that lncRNA plays important roles in various biologic processes .…”
Section: Introductionmentioning
confidence: 99%
“…14 Long non-coding RNAs (lncRNAs) are a class of transcripts with non-protein-coding capacity and 200 nucleotides in length. 15,16 A variety of studies have demonstrated that lncRNA plays important roles in various biologic processes. 17,18 Large quantities of studies have found that the disorder of lncRNA expression promotes cell invasion, proliferation and metastasis of many cancers, and affects many biologic functions.…”
mentioning
confidence: 99%
“…The lncRNA/messenger RNA gene pair AK124742 and PSMD6 presents elevated expression in human cumulus cells, the cluster of cells that surrounds the oocyte, and are correlated with oocyte maturation, fertilization, embryo quality, and clinical pregnancy outcome [ 142 ]. Furthermore, a miRNA-lncRNA analysis indicated 41 lncRNAs able to interact with oocyte microRNAs and potentially involved in the regulation of folliculogenesis [ 143 ]. In a study that investigated the role of lncRNAs in mediating the effects of β-crystallin B2 (CRYBB2) in ovary development in mice, RNA microarray profiling showed 157 differentially expressed lncRNAs and 1085 differentially expressed mRNAs between ovary tissues from wild type and CRYBB2 knockout mice.…”
Section: Long Non-coding Rnas: Expression Patterns In Tissues or Cmentioning
confidence: 99%
“…Presently, most studies have focused on the association of lncRNAs with ovarian cancer ( Norris et al, 2009 ; Mitra et al, 2017 ), and only a few reports have investigated their roles in ovarian development and follicle growth. Battaglia et al (2017) suggest that 41 lncRNAs interact with oocyte miRNAs and are potentially involved in the regulation of folliculogenesis in humans. Meanwhile, Liu et al (2018) discovered that lncRNAs/transcripts of uncertain coding potential (TU) are highly expressed in goat ovaries in the luteal phase and that this might regulate the synthesis of progesterone.…”
Section: Introductionmentioning
confidence: 99%